Study on sensory characteristics of paneer for process standardization from buffalo milk : Sensory characteristics of paneer - J. Badshah; Kumar, Sanjeev; Suryamani Kumar; B. K. Bharti; A. K. Jha (Indian Journal of Dairy Science, 2023)
Buffalo milk was utilized in a research project undertaken with the process variables for standardization of processes of manufacturing of paneer. The sensory evaluation study was described to have the effects of treatments on sensory scores for standardizing the manufacturing process. Effect of treatments on flavor score, and body and texture score were significant at P < 0.01 and P < 0.05, however, the effect of replication of sensory evaluations by Judges was non-significant. Effect of treatments on colour and appearance score was significant at P